Endogenous and Modern Innovations : Differing Perspectives - World Bank (Washington, DC, 2012)
This notes paper touches on Ethiopia's being one of nine countries Involvement in the international network PROLINNOVA (Promoting Local Innovation). The Ethiopian program set up multi-stakeholder teams in different agro climatic zones. The paper goes on to mention exhibition of local and modern innovations at the Agricultural Technologies Exhibition which was held in Mekelle, the capital of Tigray region and give examples of local innovations. Some of the technologies at the exhibition are: a water-lifting device developed by Priest Malede Abreha and displayed as a model he built himself; subsurface drainage developed to relieve waterlogged farms in the main wet season; Drip irrigation systems, improved bee hives and queen rearing; and domesticating wild bees for medicinal honey. The paper also covers how farmers assess these innovations and the differences in interests and perceptions that such innovations bring.